Acute appendicitis during the COVID-19 pandemic—changes in incidence and clinical presentation but not in patients' outcome. (8th February 2022) - Wolf, Sebastian; Schrempf, Matthias; Vlasenko, Dmytro; Schoeler, Claus; Erckmann, Frank; Von Parpart, Patrick; Paschwitz, Rieke; Anthuber, Matthias; Sommer, Florian
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic is an ongoing severe issue. Objective: The aim of this study was to compare the incidence, severity and treatment of acute appendicitis (AA) before and during the COVID-19 pandemic. Methods: A retrospective cohort analysis was conducted between January 2019 and April 2020 in one high-volume center. A comparison was performed between two groups (Group A: patients admitted with AA before the COVID-19 pandemic; Group B: patients admitted with AA at the beginning of the pandemic) in terms of the incidence of AA and clinical and pathological outcomes. The incidence of AA was also analyzed in six surrounding peripheral hospitals. Results: A total of 94 patients were identified, 54 in Group A and 40 in Group B (57% vs. 43%). Demographic data were comparable between groups. AA in Group B showed a significant higher rate of histological advanced cases (10 (18.5%) Group A vs. 20 (50%) Group B, P = 0.001) and the need for postoperative antibiotic treatment (6 (11.1%) Group A vs. 11 (27.5%) Group B, P = 0.045). During the pandemic, a higher percentage of patients were treated at peripheral hospitals (Group A: 54/111 vs. 40/126). Conclusion: During the onset of the COVID-19 pandemic there was a significant decrease of patients with AA in a high-volume center, which showed more advanced disease of AA. This significant decrease in the high-volume center correlates with an increase in patients with AA in peripheral hospitals and represents a change in patient flow during the onset of the pandemic.